Marcas de regionalidade no Instagram: análise do jornalismo independente em perfis informativos no Nordeste - SANTOS, Wyldiany Oliveira dos (2024)
As the main theme of this dissertation, independent journalism is an arrangement characterized by opposition to media conglomerates, but which also reflects contact with the community in the production of informative content. With this in mind, this study aims to identify regional characteristics in the profiles of independent journalism initiatives in the Northeast, based on posts published on Instagram. In order to do this, we have as our theoretical input concepts that address independent journalism, regional journalism, platformization and citizenship. Among the authors who will be referenced in this research are Patrício (2020), D'Andrea (2020) and Reis (2022). The survey of the initiatives analyzed was based on the maps provided by Cajueira (2023) and Agência Pública (2016). To achieve the objectives, we used the Content Analysis proposed by Franco (2005). In addition, this work is linked to cyberculture studies and is characterized as a descriptive study. The corpus for analysis comprises nine initiatives, one from each state in the Northeast, from whose Instagram profiles 353 posts were collected from the feed using the 4K Stogram program. As a result, we can point out that the Northeast is a region with more than 100 self-declared independent journalism initiatives that use regional markers linked to cultural, territorial and journalistic identity, building loyalty through the production of content based on contact with the community.